GPS Diffractive Reflectometry: Footprint of a Coherent Radio Reflection Inferred From the Sensitivity Kernel of Multipath SNR - Geremia-Nievinski, Felipe [UNESP]; Ferreira e Silva, Matheus [UNESP]; Boniface, Karen; Galera Monico, Joao Francisco [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
The validation of remote sensing environmental estimates requires knowledge of their spatial extent and resolution. Here, we consider coherent radio reflections routinely observed in ground-based global positioning system (GPS) reflectometry. Their footprint is often conceptualized in terms of the specular point (SP) and the first Fresnel zone (FFZ). Such infinitesimal point and finite zone can be generalized into a spatially continuous sensitivity kernel (SK). The SK represents a diffraction pattern, as the importance of each surface portion depends on its scattered field contribution in power and phase. We measured the SK of a GPS radio reflection under bipath reception conditions. The SK exhibited oscillations along the plane of incidence. The envelope of oscillations peaked near the SP and persisted in its decay well beyond the FFZ. Within the FFZ, sensitivity was skewed toward the antenna. This experiment suggests the feasibility of overcoming the diffraction limit and resolving features smaller than the FFZ with the exploitation of GPS diffraction patterns.
Keywords: Coherent; global navigation satellite system (GNSS); global positioning system (GPS); multipath; reflection; reflectometry